An investigation into the impact of personal branding and social media marketing on purchase intention among Tiktok Users in the Indonesia grilled sambal market of Jakarta - Sunjaya, Cumonley; Setianingsih, Rita Eka; Dema, Yosef (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2024)
Nowadays, marketing strategies that leverage personal branding and social media significantly shape customer behavior in several industries. The effects on the Jakarta-based TikTok user market for Indonesian Grilled Sambal goods are the primary subject of this research. For this study, we used Google Forms to poll people who met certain age, TikTok, and Iben Ma familiarity/product/influencer requirements. Perceptions of personal branding and social media marketing were examined using descriptive statistics, focusing on how they affected purchase intention. The results showed that the target audience had favorable impressions and a strong propensity to buy, and the study used traditional assumption testing to validate a regression model. The results show how much of an impact these characteristics have on buying habits. The study highlights the revolutionary impact of social media marketing on influencing customer behavior and brand perceptions, drawing from theories such as Social Identity Theory and the Elaboration Likelihood Model of Persuasion. With these findings in hand, marketers targeting specific food niches can improve their social media engagement with customers. The paper goes on to say that more research into the relationship between niche market customer behavior, personal branding, and social media should be pursued.